2011
DOI: 10.1016/j.semcdb.2011.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic mechanisms in gliovascular coupling

Abstract: Regional elevations in cerebral blood flow (CBF) often occur in response to localized increases in cerebral neuronal activity. An ever expanding literature has linked this neurovascular coupling process to specific signaling pathways involving neuronal synapses, astrocytes and cerebral arteries and arterioles. Collectively, these structures are termed the "neurovascular unit" (NVU). Astrocytes are thought to be the cornerstone of the NVU. Thus, not only do astrocytes "detect" increased synaptic activity, they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 76 publications
(130 reference statements)
0
49
0
Order By: Relevance
“…Transient withdrawal of glucose, the major energy substrate for neurons, as well as removal of amino acids from the culture medium results in mitochondrial depolarization, reduced ATP production, and the development of delayed tolerance against various insults, such as OGD, glutamate excitotoxicity, and exogenous hydrogen peroxide (63). Breakdown products of ATP: adenosine, AMP, ADP, as well as ATP itself, are vasoactive stimuli in cerebral arteries (36,123).…”
Section: Role Of Mitochondria In Cellular Protectionmentioning
confidence: 99%
“…Transient withdrawal of glucose, the major energy substrate for neurons, as well as removal of amino acids from the culture medium results in mitochondrial depolarization, reduced ATP production, and the development of delayed tolerance against various insults, such as OGD, glutamate excitotoxicity, and exogenous hydrogen peroxide (63). Breakdown products of ATP: adenosine, AMP, ADP, as well as ATP itself, are vasoactive stimuli in cerebral arteries (36,123).…”
Section: Role Of Mitochondria In Cellular Protectionmentioning
confidence: 99%
“…It should be noted that P2Y 1 Rs, found on the glia limitans and on vascular endothelium, are also important for ischaemic regulatory processes; for example, endothelial P2Y 2 Rmediated dilatations of rat middle cerebral artery in response to uridine-5′-triphosphate (UTP) were potentiated after ischaemia-reperfusion, while P2Y 1 R-mediated dilatation was simultaneously attenuated [206,207]. Not only purine but also pyrimidine nucleotides appear to be released during ischaemia; the UTP-induced activation of P2Y 4 Rs causes cell death in human neuroblastoma cells [208].…”
Section: Ischaemia/hypoxiamentioning
confidence: 99%
“…For example, studies using human umbilical vein endothelial cells showed that these cells could develop BBB properties when cocultured with astrocytes, which implies that astrocytes secrete trophic factors critical to maintenance of the BBB phenotype (Hayashi et al, 1997). Astrocytes may be involved in transient regulation of cerebral microvascular permeability (Ballabh et al, 2004), in particular via dynamic Ca 2+ signaling between astrocytes and the endothelium via gap junctions and purinergic transmission (Goldberg et al, 2010;Pelligrino et al, 2011). Recent evidence also suggests that astrocytes may play a critical role in regulating water and ion exchange across the brain microvascular endothelium (Abbott et al, 2006;Mathiisen et al, 2010).…”
Section: B Blood-cerebrospinal Fluid Barriermentioning
confidence: 99%